Mental health status and social communication skills among adults suspected with Attention Deficit Hyperactivity Disorders (ADHD) symptoms - Abdul Mu'iz, Nur Shafiqah; Jusoh, Masnira (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2023)
Introduction: To date, limited epidemiological data are available concerning the impact of attention deficit hyperactivity disorders (ADHD) and mental health issues on the social communication skills of adults in Malaysia. It is crucial to comprehend the relationship between ADHD symptoms and how they may affect individuals’ mental health status and social communication skills. Objective: The aims of the current study are to ascertain the prevalence of undergraduate students suspected of having ADHD, experiencing depression-anxiety-stress, and exhibiting poor social communication skills. Furthermore, this study seeks to compare the mental health status and social communication skills of adults with and without ADHD symptoms. Additionally, this study also aims to examine the relationships between mental health status, ADHD symptoms, and social communication skills among undergraduate students in higher education institutions. Method: A cross-sectional study design was utilized among undergraduate students at one of the universities in Pahang. The study subjects were recruited through snowball sampling and data collection was conducted over a period of approximately three months. A total of 186 participants completed self-reported demographic information, self-rating questionnaires, including the Depression Anxiety and Stress Scale 21 (DASS-21), Adult ADHD Self-Report Scale (ASRS v1.1) and Conversational Skills Rating Scale (CSRS), via an online questionnaire platform (Google Forms). Results: It was found that 39% of undergraduate students are suspected to have ADHD symptoms. A high prevalence of depression, anxiety, and stress, at 69.0%, 75.9%% and 49.7%, respectively, was also observed. Significant differences (p<0.05) were found in depression-anxiety-stress and social communication skills between students with and without ADHD symptoms. There were low to moderate correlations, ranging from -0.08 to 0.61, between communication skills, mental health domains, and ADHD subdomains. Conclusions: ADHD symptoms, mental health status, and social communication skills between undergraduate students with and without ADHD symptoms were statistically different. There were significant associations between ADHD symptoms, depression, anxiety, and stress. However, only a weak association was revealed between ADHD symptoms and social communication skills among undergraduate students in Pahang.